Dinamika Konsumsi dan Inflasi Dalam Tren Ekonomi di Bulan Ramadhan - I, Imron (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This paper explains the dynamics of consumption and inflation in economic trends during the month of Ramadan. The month of Ramadan significantly influences consumption patterns and inflation rates. The surge in demand for essential goods, food, and other consumer products often leads to significant price increases. This study aims to analyze the dynamics of consumption and inflation during Ramadan and the efforts to control them. Using a qualitative approach, this research examines consumption trends, the impact of inflation on purchasing power, and strategies to maintain economic stability. The findings indicate that increased consumption, when not matched by adequate supply, contributes to higher inflation, particularly in the food sector. Moreover, the